Scoping Review of Employment and Psychiatric Comorbidities in Adults With Childhood-Onset Epilepsy. - Ando, Saeko; Iwase, Kimiko; Katsuda, Hitomi (Journal of Japan Academy of Nursing Science, 2025)
Objective: To review the literature on employment and psychiatric comorbidities in adults with childhood-onset epilepsy and to investigate study trends and challenges in transition support. Methods: Databases utilized included PubMed, CINAHL, and Ichushi WEB. The inclusion criteria for literature selection required that the subjects be patients with childhood-onset epilepsy and that the literature describe psychiatric symptoms and employment. Results: A total of 27 pieces of literature were analyzed. Four studies indicated a significant association between psychiatric symptom comorbidity and employment, whereas four studies reported no association, presenting contradictory results across the literature. Furthermore, patients' quality of life was correlated with the presence of psychiatric symptoms, employment status, seizure frequency, and side effects of antiepileptic drugs. Intervention research indicates that group sessions and telephone contact with nurses are effective in alleviating psychiatric symptoms. Conclusion: There is a need for qualitative research on negative experiences at work and on readiness to cope with stress and self-management during the transition period.